Emerging Threats in the Age of Pandemics: A Focus on COVID-19 and the Novel Sub-Variant EG 5 ("Eris"): Review Article - Alsayed, Raghda; Thamer, Hamsa; Hameed, Seenar; Kadhom, Mohammed; Hairunisa, Nany; Amalia, Husnun; Mashabi, Yasmine; Ahmed, Dina; Mahdi, Sarah; Husain, Amani; Salman, Israa; Yousif, Emad (Jurnal Biomedika dan Kesehatan, 2024)
This paper draws attention to a recently identified sub-variant of SARS-CoV-2 known as EG 5, colloquially named "Eris," designated by the World Health Organization (WHO) as a variant of interest. The organization has urged nations to monitor and respond to the spread of this sub-variant since its identification on February 17, 2023. The discovery of the EG 5 variant, a sublineage of the Omicron variant, has introduced new challenges. Designated a "variant of interest" by the WHO, EG 5 carries distinctive genetic mutations, including an additional F456L amino acid mutation in the spike protein. Global prevalence has doubled, raising concerns about increased transmissibility. Although specific symptoms of EG 5 are not yet fully characterized, the variant has spread to 51 countries, with over 7,000 reported cases by August 15, 2023. The manuscript also explores the unique situation in Iraq, where, as of August 17, 2023, no EG 5 cases have been officially recorded. However, challenges such as self-treatment at. As the world grapples with the ongoing challenges of the COVID-19 pandemic, understanding the dynamics of emerging variants is crucial for effective public health responses and the development of targeted interventions.